2005
DOI: 10.1038/sj.pcan.4500782
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and management of bicalutamide-induced gynecomastia and breast pain: randomized endocrinologic and clinical studies with tamoxifen and anastrozole

Abstract: A randomized, double-blind, placebo-controlled multicenter trial involving 107 men receiving bicalutamide ('Casodex') 150 mg/day therapy following radical therapy for prostate cancer assessed tamoxifen ('Nolvadex') 20 mg/day and anastrozole ('Arimidex') 1 mg/day for the prophylaxis and treatment of gynecomastia/breast pain. Tamoxifen, but not anastrozole, significantly reduced the incidence of gynecomastia/breast pain when used prophylactically and therapeutically. Serum testosterone levels increased with tamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 14 publications
1
56
0
4
Order By: Relevance
“…12 Tamoxifen was more effective than RT for preventing bicalutamide induced gynecomastia and breast pain. Our positive findings are in agreement with prior studies with different treatment schedules, such as those of Boccardo 12 and Saltzstein 13 et al, who administered 20 mg tamoxifen daily, and those of Eaton et al, who administered 20 mg weekly. 16 The incidence of gynecomastia in our trial was 34% after RT, lower than that reported by Tyrrell et al, who noted gynecomastia in 52% of the RT group, 14 and similar to that reported by Widmark et al, who observed gynecomastia in 28% of irradiated patients.…”
Section: Discussionsupporting
confidence: 83%
“…12 Tamoxifen was more effective than RT for preventing bicalutamide induced gynecomastia and breast pain. Our positive findings are in agreement with prior studies with different treatment schedules, such as those of Boccardo 12 and Saltzstein 13 et al, who administered 20 mg tamoxifen daily, and those of Eaton et al, who administered 20 mg weekly. 16 The incidence of gynecomastia in our trial was 34% after RT, lower than that reported by Tyrrell et al, who noted gynecomastia in 52% of the RT group, 14 and similar to that reported by Widmark et al, who observed gynecomastia in 28% of irradiated patients.…”
Section: Discussionsupporting
confidence: 83%
“…120,121 Tamoxifen is the most effective medical therapy for gynecomastia and/or mastodynia. 122,123 Breast reduction surgery may benefit the occasional man with severe breast symptoms that are refractory to medical treatment.…”
Section: Gynecomastia and Mastodyniamentioning
confidence: 99%
“…No hubo diferencias en la respuesta terapéuti-ca entre Gi fisiológica puberal y no puberal (patológica e idiopática del adulto), lo que sugiere en ambos casos la existencia de un desbalance 28,29 , lo que supondría que el bloqueo del receptor estrogénico es más importante que la disminución del estrógeno plasmático e intramamario. Fue exitoso el combinar tamoxifeno con el antiandrógeno que produjo Gi durante la terapia del acné.…”
Section: Discussionunclassified
“…Fue exitoso el combinar tamoxifeno con el antiandrógeno que produjo Gi durante la terapia del acné. Resultados similares se reportaron con tamoxifeno-flutamida 30 y tamoxifeno-bicalutamida 29 en Gi desarrollada durante terapia con antiandrógenos en cáncer prostático. Se ha señala-do que las Gi con diámetro máximo ≥ 4 cm no regresarían con antiestrógenos 18 , nuestro 52% de desaparición de Gi ≥ 4 cm indicaría que el mayor tamaño no impide utilizarlos.…”
Section: Discussionunclassified